Modelling stress evolution and voiding in advanced copper nano-interconnects under thermal gradients. (August 2020) - Zahedmanesh, Houman; Croes, Kristof
Abstract: As the chip power densities increase radically with scaling, thermal gradients are predicted to become a major reliability concern in interconnects compatible with the 3 nm technology node and beyond. In this study, the impact of temperature gradients on the reliability of Cu nano-interconnects with highly scaled linewidth of 10 nm is simulated using a Korhonen-type modelling framework previously calibrated for electromigration predictions. ∆T dictates the stress distribution at steady state while dT / dx along the interconnect governs the stress evolution rate. It is shown that a linear temperature profile with a ∆T of >25 °C can generate voiding by thermomigration alone in these narrow lines. The adverse impact of thermal gradients by thermomigration and also by thermally induced flux divergence points are explored, showing a 20% drop of j max in the presence of a ∆T of 10 °C and secondary nucleation sites along the line depending on temperature distribution. Immortality of Cu nano-interconnects to electromigration in the presence of thermal gradients was assessed whereby a thermally adjusted jL c is found relevant depending on the direction of electron flow with respect to temperature gradient. Highlights: A ∆T of >25 °C can generate voiding by thermomigration alone. 20% drop of j max in the presence of a ∆T of 10 °C is predicted. Secondary nucleation sites generated by thermally induced flux divergence points. 36% drop of ( jL c ) by exposure to a ∆T of 10 °C is predicted.